Pemberdayaan Kelompok Tani melalui Inovasi Pestisida Nabati Berbasis Limbah Kulit Bawang Merah dan Bawang Putih - Olivia Wardhani; Tsany Nur Farras; Hisyamudin Assyauqi; Nufthy Anggita Herlina; Endras Larasati; Maulida Ramdani; Yunia Hafidhoh; Erin Vandana; Ersa Agustina Eka Putri; Riza Matholiul Umam (Penerbit Goodwood, 2026)
Purpose: This community service program aims to evaluate the effectiveness of participatory training in empowering Banaran Village farmers to adopt plant-based pesticides based on onion peel waste, in order to reduce dependence on synthetic chemical pesticides. Research Methodology: This participatory research involved 12 participants from nine farmer groups. Evaluation used pre- and post-tests (10 essay questions), practical skills observations, and an adoption interest questionnaire. Data analysis was conducted using paired t-tests and percentages. Results: There was a significant increase in knowledge, with the average score increasing from 42.3 (pretest) to 86.5 (posttest). Ninety-one-six percent of participants (11 people) successfully formulated the correct ratio, and 83.3% (10 people) expressed a high level of interest in adopting the technology. Conclusions: This program is effective in improving farmers' literacy and technical skills regarding botanical pesticides. Utilizing local waste has the potential to lower production costs and support sustainable agriculture. Limitations: This research was limited to one village with a short duration, a limited number of participants, no laboratory tests were conducted on the quality of the extract, and the evaluation only covered short-term impacts. Contributions: This research contributes to the field of sustainable agriculture and organic waste management, and can be a model for community empowerment based on local potential for other villages.